2022
DOI: 10.3390/ijerph192416405
|View full text |Cite
|
Sign up to set email alerts
|

In Caring for Older People in Low- and Middle-Income Countries, Do Older Caregivers Have a High Level of Care Burden and Psychological Morbidity Compared to Younger Caregivers?

Abstract: Caregivers have become older as longevity increases. Caregiving for older people can cause burdens and psychological morbidity, which are the chronic stresses perceived by informal caregivers. This study aimed to compare the levels of care burden and psychological morbidity between older and younger caregivers in low- and middle-income countries. A cross-sectional survey was conducted in Cuba, the Dominican Republic, Peru, Venezuela, Mexico, Puerto Rico, and China. Data were collected by the 10/66 Dementia Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Furthermore, the negative emotions associated with long-term care, the medical costs associated with the treatment of the disease, and the complications caused by improper management all place a great burden on family caregivers, creating a vicious cycle. 50 Therefore, community home-based aging institutions can provide more opportunities for old people with chronic NCDs to participate in society and learn and use various electronic media such as health platforms, WeChat official account, TikTok, community radio to popularize knowledge about diseases, reasonable diet, mental health, physical exercise, medication matters, emergency disposal and other knowledge, to improve the e-health literacy and disease self-management ability of old people. As shown by the serial multiple mediation model, e-health literacy indirectly mediates the relationship between social support and self-management in old people, supporting Hypothesis 2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the negative emotions associated with long-term care, the medical costs associated with the treatment of the disease, and the complications caused by improper management all place a great burden on family caregivers, creating a vicious cycle. 50 Therefore, community home-based aging institutions can provide more opportunities for old people with chronic NCDs to participate in society and learn and use various electronic media such as health platforms, WeChat official account, TikTok, community radio to popularize knowledge about diseases, reasonable diet, mental health, physical exercise, medication matters, emergency disposal and other knowledge, to improve the e-health literacy and disease self-management ability of old people. As shown by the serial multiple mediation model, e-health literacy indirectly mediates the relationship between social support and self-management in old people, supporting Hypothesis 2.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that home caregivers experienced slightly lower caregiver-related quality of life compared to caregivers in LTC facilities. Several caregiver characteristics, such as being female, younger in age, cohabiting with the care recipient, bearing a higher objective burden, reporting lower self-rated health, and receiving more support, were associated with an increased burden and/or decreased caregiver-related quality of life [28].…”
Section: Differences In the Caregiving Experiences And Mental And Phy...mentioning
confidence: 99%
“…Care-recipient factors influencing care burden were physical disability (11)(12)(13), mental dependency (11), and behavioral and psychological symptoms of dementia (13). Caregiver factors were gender (11), age (13)(14)(15), satisfaction with care (16), caring time (10,17,18), duration of caregiving (11), care attitude (19), and stress (6,11). Lastly, the utilization of community services (20) and perceived social support (11,20) were social factors reported to affect caregiver burden of care.…”
Section: Introductionmentioning
confidence: 99%